Creating Knowledge/ Breaking the Monopoly; Research Methods, Participation, and Development. Working Paper No. 1 - Hall, Budd L. (Distributed by ERIC Clearinghouse, Society of Participatory Research in Asia, 1982)
Combining community participation in decision making with methods of social investigation, participatory research focuses on involvement of the subjects of the research in the research process. Adult educators are exploring this research method which, unlike quantitative research, serves the needs of individuals and not those of policy makers who need convenient, portable information and researchers who survive economically by collecting, packaging, and selling knowledge. Renewed attention has been brought to the weaknesses of the survey appoach, the most commonly used research method. It oversimplifies social reality and is therefore inaccurate; is often alienating, dominating, or oppressive in character; does not provide easy links to possible subsequent action; and uses methods which are not consistent with the principles of adult education. Work continues on finding alternative strategies, one of which is participatory research. This concept rests on the premises that a research process can immediately and directly benefit and is part of a total educational experience for the population involved in the entire dialectic process, that its object is the liberation of human creative potential and the mobilization of human resources for the solution of social problems, and that it has ideological implications. As an example, a Tanzanian village used this process to improve low-cost grain storage. (YLB)